MENINGKATKAN KUALITAS PADA PROSES PENGISIAN PULSA ELEKTRIK DENGAN MENGGUNAKAN METODE SIX SIGMA - Johnny Harjono; Jeddy J. Sardjono (Bina Nusantara University, 2010)
In globalization era recently, communication became a very important needed, not only a few industries engaged in telecommunications to compete getting a lot of customers, it is also done by the distribution industry of electrical pulses, one of them is GrahaPulsa.com. GrahaPulsa.com should notice to customer satisfaction in the process of charging the pulse. Recently GrahaPulsa.com has problems which is the slowness off reload transaction processing, thereby affected customer satisfaction. This significantly effect in the sales process pulses. Therefore, is used a concept called